INTERDISCIPLINARY CONTEXTUALIZATION (ICon) LESSONS IN TEACHING SENIOR HIGH SCHOOL MATHEMATICS - Pescuela, Edward B; Goyena, Jocelyn F (PEOPLE: International Journal of Social Sciences, 2020)
The study aimed to investigate the effects of Interdisciplinary Contextualization (ICon) lessons in teaching functions and their graphs. The study utilized mixed methods design to describe the features of interdisciplinary contextualization approach and to identify its effect to students’ academic performance. The lessons were implemented to thirty-eight Grade 11 public school students in Albay, Philippines. The features identified are thematic, use of local context, problem-based learning, inquiry-based learning and collaborative learning. The features identified came from the teachers interviewed who uses the approach and the researcher’s pertinent document analyses. The problems in the lessons used these features in synthesizing concepts that served as an axis of connection among disciplines. The results obtained from pretest and posttest scores of students revealed that there was a significant difference in favor of the implementation. Consequently, interdisciplinary contextualized lessons helped students to be real-life problem solvers, developed cultural awareness by citing relevant in-context problems and helped connect previously learned concepts from other disciplines. Educators must be aware that Mathematics is part of the students’ personal life, community and cultural heritage. Thus, interdisciplinary contextualization approach relate the teaching and learning process within specific communities and culture for meaningful learning experiences of the students. This approach that uses integrated lessons in Mathematics make the teaching and learning more accessible, relevant, and meaningful to every students that would further develop 21st century skills.